Pesticide Poisoning Among Agriculturists of Dharwad District: A Study - Gyanappa Huddar*, Purnanand Nagappa Sangalad, Malakajappa (Recent Research in Science and Technology, 2010)
Abstract Pesticide poisoning cases between 2003-2009 have been surveyed to understand the pattern of poisoning cases among farmers of Dharwad district. Total 39 poisoning cases were studied from OPD (Out Patient Department) to IPD (In Patient Department), followed from admission to recovery or death in a systematic manner. All these cases were analyzed with an objective of knowing age distribution of victims, commonest type of poisoning, the manner of poisoning, and also the rural and urban trends. Among 39 cases, male 31 cases (79.48%) predominated females 8 cases (20.51%) with majority (41.02%) belonging to 41-50 yrs age group. The commonest poison encountered was the Organophosphorous compounds (48.71%). Suicide (79.48%) was the commonest manner than accidental poisoning. Agricultural farmers with rural background, belonging to lower socio-economic strata were the commonest victims (79.48%) compared to others. Keywords: Poisoning cases, Organophosphorous compounds, Suicide, Farmers, Agricultural